Gender Issues in Cooperative Societies of Ilam - Thapa, Bhupal Krishna (Journal of Advanced Academic Research, 2017)
Cooperative is an organization run by the similar professional people for the betterment of their socio-economic uplift with common goals in the democratic way. The success or failure of any cooperative depends upon the members’ role. If the female memberships are grown, and opportunities are given in governance, cooperative societies will be successful. The present study was conducted to explore the status of cooperative female members’ memberships, and governance like board of directors and job opportunities provided by the concern cooperatives in Ilam, Nepal. The nature of the study was quantitative and qualitative implying survey method and in-depth interview. There were 226 cooperative members from three types of cooperatives: Savings and Credit, Tea, and Dairy cooperatives. The present study showed that the majority of the female members were deprived of their basic rights of participating in AGM, board of directors and office works from their concern cooperatives. Thus, the cooperatives are requested to encourage their female members in memberships, and governance. Journal of Advanced Academic Research Vol. 3, No. 2, 2016, page: 22-28